Fear of injury in gymnastics: Self-efficacy and psychological strategies to keep on tumbling - Chase, M. A.; Magyar, M. T.; Drake, B. M. (Journal of Sports Sciences, 2005)
The aim of this study was to examine female gymnasts' fear of injury, their sources of self-efficacy and the psychological strategies used to overcome their fears. The participants were 10 female gymnasts aged 12 - 17 years. They had all taken part in competitive gymnastics and had experienced some type of injury during their careers. Individual interviews were conducted using a structured interview guide. Data were analysed using an inductive content analysis. The results indicated that gymnasts were most fearful of injuries because of the difficulty in returning from an injury and being unable to participate in practices and competitions while injured. Gymnasts described aspects of their past performance experience, such as success, consistency and communication with significant others, as important sources of self-efficacy. Some examples of psychological strategies used to overcome their fear of injury were mental preparation (e.g. imagery, relaxation), just "going for a skill" and the coaches' influence.